Headings on spiritual knowledge (the second part, chapters 1-3) - Isaak Ninive, Bischof, Heiliger 640-700 (St Vladimir's Seminary Press, 2022)
"Appearing for the first time in English, this volume contains a translation of the Kephalaia Gnostika, the first three chapters of the recently-discovered "Second Part" of the corpus of St Isaac of Nineveh (or "the Syrian"). This text touches upon many aspects of the "life of stillness," that is, the spiritual life of hermits who would later be called hesychasts, and the author explores and explains the various levels and forms of prayer and spiritual experience from his own experience"--
Keywords: Syrische Kirche von Antiochien; Geschichte 680; Spirituelle Erfahrung; Orthodoxe Theologie; Gebet; Asceticism / Early works to 1800; Spiritual life / Christianity / Early works to 1800; Sermons, Medieval; Ascétisme / Ouvrages avant 1800; Vie spirituelle / Christianisme / Ouvrages avant 1800; Sermons médiévaux; Asceticism; Spiritual life / Christianity; Early works; Quelle